Manajemen Pendidikan dalam Kacamata (Pandangan) Al-Qur’an - Dian Herdiana; Dida Hidayat; Anggun Gunawan (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
Al-Qur'an is a way of life for all time, which is relevant in various aspects of life. At first glance, the Qur'an discusses issues of belief, worship, morals, lawful and unlawful, but more than that, the Qur'an also discusses issues of science. Among other things related to education issues, including the scope and Management of Education. The word "Yudabbiru" which means to regulate, should be the basis that the Qur'an there does discuss God's settings for His creation, including managing the affairs of His creatures. Departing from the fact that humans as vicegerents of God on earth have the duty and obligation to manage, utilize, and prosper this earth. Education here includes the implementation and management of education properly and correctly. Al-Qur'an and Hadith as the foundation of Islamic education management with the principles of Tawheed, Khalifah and Amanah. Furthermore, the familiar function is called management Planning, Organizing, Motivating and Controlling, such as the teachings of the Qur'an, that in life and living, humans must have planning, organising, unity and mutual cooperation. Apart from that, it must also be able to move others to do or carry out both motivation, advice and guidance. thus need to be controlled and monitored in order to get maximum results